Answer to Question #313824 in Complex Analysis for Jyo

Question #313824

Evaluate โˆซf ๐‘œ๐‘ฃ๐‘’๐‘Ÿ ๐‘ where ๐‘“( ๐‘ง )= ๐‘ฅ^2 + ๐‘–๐‘ฆ^2 where c is given by ๐‘ง (๐‘ก )= ๐‘ก^2 + ๐‘–๐‘ก^2, 0 โ‰ค ๐‘ก โ‰ค 1

1
Expert's answer
2022-03-20T06:43:38-0400

โˆซCf=[z(t)=t2+it2dz(t)=(2t+2it)dt=2(1+i)tdtf(z)=x2+iy2==(t2)2+i(t2)2==(1+i)t4]=โˆซ01(1+i)t4โ‹…2(1+i)tdt==2(1+i)2โˆซ01t5dt=2โ‹…2i6=23i\int_C{f}=\left[ \begin{array}{c} z\left( t \right) =t^2+it^2\\ dz\left( t \right) =\left( 2t+2it \right) dt=2\left( 1+i \right) tdt\\ f\left( z \right) =x^2+iy^2=\\ =\left( t^2 \right) ^2+i\left( t^2 \right) ^2=\\ =\left( 1+i \right) t^4\\\end{array} \right] =\int_0^1{\left( 1+i \right) t^4\cdot 2\left( 1+i \right) tdt}=\\=2\left( 1+i \right) ^2\int_0^1{t^5dt}=\frac{2\cdot 2i}{6}=\frac{2}{3}i


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog